INTEGRITAS NILAI BUDAYA PADA PERADABAN ORGANISASI MASYARAKAT NAHDLATUL ULAMA DALAM MEMBANGKITKAN ERA BARU : (Kajian Kebudayaan Terhadap Peradaban Ormas NU di Indonesia) - Mimar, Neng Hilma; Seva, Kristining (FOCUS, 2024)
This research aims to analyze the Nahdlatul Ulama (NU) movement in building a superior era, evaluate the implementation of NU's cultural values to society, especially the younger generation, and identify the positive and negative impacts of NU movement development in the new era. The research method used is descriptive qualitative with a narrative research approach and utilizes theoretical frameworks from Norbert Elias and F. Ratzel. Data were obtained through literature study, then analyzed using data reduction techniques, data presentation, and conclusions. The results show that the NU movement in revitalizing the civilization of the new era is directed through the preaching concepts inherited from previous scholars, with strategic steps covering religious, political, economic, and social fields. NU places belief as a sub-dominant to encourage aspects of community life based on religious teachings. The positive impact is the preservation of NU's cultural values, while the negative impact is the lack of adaptation to other religious groups. In conclusion, NU applies cultural values into its integrity by referring to the legacy of previous scholars, especially in building the concept of Islam Nusantara, as NU's effort in facing globalization.